THE INFLUENCE OF POWNERSHIP INCOME AND GOLD PRICES ON RAHN'S FINANCING IN PT. PAWNSHOP SHARIA BRANCH LANGSA (YEAR 2014-2019) - Firda Ananda Lubis; Pandapotan Ritonga (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to determine the effect of pawnshop income and gold prices on the distribution of Rahn's financing at the Langsa sharia pawnshop 2014-2019. The research method used was quantitative research using secondary data. The population in this study were all financial statements of the Langsa branch of Islamic pawnshops in 2014-2019. The sample in this study is the quarterly financial report of the Langsa branch of Islamic pawnshops in 2014-2019. The dependent variable of this research is the distribution of Rahn's financing. The independent variables include: pawnshop income, gold price. For the data analysis method using multiple linear regression analysis.So it can be concluded that the independent variables of pawnshop income and the price of gold (simultaneously) have an effect on the rahn financing variable.